Pengaruh Gadget Terhadap Pendidikan Seks Pada Anak di SDN Pasirlayung 1 Kecamatan Cimenyan Kabupaten Bandung - Ela Hayati; M.Fadlani Salam; Supala (Gunung Djati Conference Series, 2022)
The condition of the COVID-19 pandemic requires that learning be done online, which causes students to learn to use gadgets. The subject matter that children are looking for on the internet without realizing it, many pornographic sites appear that can be easily accessed by children. Warisyah (2015), argues that gadgets are electronic devices used as information media, learning media and entertainment media. Pornographic sites are very popular and easily accessible by all people. Sex education should be given to children to provide understanding and changes that occur in him. Nina Surtiretna provides knowledge related to biological, psychological and psychosocial changes as a result of the growth and development of human beings. This study uses a quantitative research approach. The population and sample in this study were all students of class V and VI of SDN Pasirlayung 1, Cimenyan District, Bandung Regency, totaling 75 students. The data obtained p value = 0.19 so that it can be said that gadgets have an influence on sex education in children by 33% in class V and VI students at SDN Pasirlayung 1, Cimenyan District, Bandung Regency.